# function ( partial fraction)

posted by .

if f(x) ax^2+bx+c , g(x) :1/3x^2+2 and fg(x)= 18x^4+24x^2+11/(3x^2+2)^2. find a ,b and c

• function ( partial fraction) -

Well, thinking fg(x) means f(x) * g(x) I get no consistent solution. So, making
fg(x) = f(g(x)) we have

f(g) = ag^2 + bg + c
= a/(3x^2+2)^2 + b/(3x^2+2) + c
= [a + b(3x^2+2) + c(3x^2+2)^2] / (3x^2+2)^2

= 9cx^4 + (12c+3b)x^2 + (4c+2b+a)
= 18x^4 + 24x^2 + 11

That makes c=2, b=0, a=3, so f(x) = 2x^2 + 3

• function ( partial fraction) -

solve it in a way am goin 2 understand

## Similar Questions

1. ### BobPursley..here it is:

Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common denominator is: (3x+4)(x+1) (x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4) [(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4) (x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4) x^2 - 18x^2 = -17x^2 -x …
2. ### Algebra (Re.: Reiny)

The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 + b^2)/ab …
3. ### Algebra

checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
4. ### Math

Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2
5. ### algebra

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
6. ### Math

Express in partial fraction.7x^2-18x-7 divided by (x-4)(2x^2-6x+3)
7. ### Math

Express in partial fraction.7x^2-18x-7 divided by (x-4)(2x^2-6x+3)
8. ### partial fraction

if f(x) ax^2+bx+c , g(x) :1/3x^2+2 and fg(x)= 18x^4+24x^2+11/(3x^2+2)^"
9. ### Math

Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+18x-36
10. ### Math

(2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?

More Similar Questions